PERAN UN WOMEN DALAM MENANGANI KRISIS KEMANUSIAAN TERHADAP PEREMPUAN DI PALESTINA - Luthfiya, Anggira Zahra; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research analyzes the role of UN Women in addressing the humanitarian crisis that affecting women in Palestine. The humanitarian crisis experienced by Palestinian women has worsened following the attacks on October 7, 2023. This conflict led to retaliatory strikes by Israel, impacting hygiene, health, and women's organizations in Palestine. As an international organization dedicated to fulfilling the fundamental rights of women, UN Women has launched initiatives and undertaken various efforts to address the humanitarian crisis faced by Palestinian women, particularly in the aftermath of the October 7, 2023, attacks. This research on the role of UN Women in Palestine employs a qualitative method, utilizing data collection through library research, including books, journals, official reports, and online sources. This research also applies Alexander Wendt's Constructivist Perspective and Clive Archer's International Organization Theory. Based on this study, it is concluded that the primary role of UN Women in addressing the humanitarian crisis for women includes implementing the Sixth Month Framework Program aimed at managing the humanitarian crisis during the period from November 2023 to April 2024. Following the completion of this program, UN Women continues its efforts to address the humanitarian crisis affecting Palestinian women through official publications focusing on the crises in Water, Sanitation, and Hygiene (WASH), health, and Women-Led Organizations (WLO). Keywords: UN Women, Humanitarian Crisis, Palestinian Women